Systematic review of perception of barriers and facilitators to chronic disease self‐management among older adults: Implications for evidence‐based practice. Issue 3 (15th January 2022) - Nguyen, Thi Ngoc Minh; Whitehead, Lisa; Saunders, Rosemary; Dermody, Gordana
Abstract: Background: An aging population has contributed to an increased prevalence in chronic disease. To empower patients, healthcare systems are shifting toward chronic disease self‐management. However, no review on how older adults self‐manage chronic disease and the barriers and facilitators they experience has been published. Aims: To explore barriers and facilitators perceived by older adults during the process of self‐managing chronic disease. Methods: A systematic review of qualitative literature was performed using the Joanna Briggs Institute methodology. The literature search was conducted using Ovid databases (MEDLINE, CINAHL with full text, and PsycINFO) for the period of 1988–2020. All records were screened using predetermined eligibility criteria. The critical appraisal instrument QARI (Qualitative Assessment and Review Instrument) was employed to assess the quality of the included studies. Data from the included papers were extracted using the QARI data extraction tool. Extracted data were then synthesized to produce final sets of themes and sub‐themes relating to the review question. Results: A total of 267 abstracts were screened, and 13 studies reporting barriers and facilitators perceived by older adults during the process of managing chronic diseases were included in the review. Physical and cognitive decline, low‐health literacy, culture, and relationships with healthcare professionals were described as barriers. Facilitators were described as resources that supported disease self‐management and included family, social networks, healthcare professionals, and religious beliefs. Linking evidence to action: This study highlights the importance of understanding the patients' perspectives of the barriers and enablers of self‐management of chronic illness for health professionals across settings. Understanding barriers and facilitators to chronic disease self‐management will support health professionals to identify strength‐based approaches to self‐management that meet the needs of individual older adults.